Targeting Inflammation to Prevent Cardiovascular Disease in Chronic Rheumatic Diseases: Myth or Reality? - Bartoloni, Elena; Alunno, Alessia; Valentini, Valentina; Luccioli, Filippo; Valentini, Eleonora; La Paglia, Giuliana Maria Concetta; Leone, Maria Comasia; Cafaro, Giacomo; Marcucci, Elisa; Gerli, Roberto (Frontiers in Cardiovascular Medicine, 2018)
Evidence for increased risk of cardiovascular morbidity and mortality in chronic inflammatory rheumatic diseases has accumulated during the last years. Traditional cardiovascular risk factors contribute in part to the excess of cardiovascular risk in these patients and several mechanisms, including precocious acceleration of subclinical atherosclerotic damage, inflammation and immune system deregulation factors, have been demonstrated to strictly interplay in the induction and progression of atherosclerosis. In this setting, chronic inflammation is a cornerstone of rheumatic disease pathogenesis and exerts also a pivotal role in all stages of atherosclerotic damage. The strict link between inflammation and atherosclerosis suggests that cardiovascular risk may be reduced by rheumatic disease activity control. There are data to suggest that biologic therapies, in particular TNFα antagonists, may improve surrogate markers of cadiovascualr disease and reduce CV adverse outcome. Thus, abrogation of inflammation is considered an important outcome for achieving not only control of rheumatic disease, but also reduction of cardiovascular risk. However, the actual effect of anti-rheumatic therapies on atherosclerosis progression and CV outcome in these patients is rather uncertain due to great literature inconsistency. In this paper, we will summarize some of the main mechanisms linking the inflammatory pathogenic background underlying rheumatic diseases and the vascular damage observed in these patiens, with a particular emphasis on the pathways targeted by currently available therapies. Moreover, we will analyze current evidence on the potential atheroprotective effects of these treatments on cardiovascular outcome pointing out still unresolved questions.